Serum Interleukin-18 Expression in Children With Bronchial Asthma - Hossny, Elham M (World Allergy Organization, 2009)
BACKGROUND: Interleukin 18 (IL-18) is reported to have regulatory functions on Th1 and Th2 cytokine production and proinflammatory effects through promoting recruitment of memory Th1 cells to inflammatory sites. We sought to investigate the expression of the serum IL-18 in childhood bronchial asthma in relation to disease activity and severity. METHODS: Serum IL-18 was measured by enzymatic immunoassay in 25 asthmatic children during exacerbation and after complete quiescence of symptoms and signs. The results were compared to those of 35 nonallergic age- and sex-matched children. RESULTS: Serum IL-18 levels during asthma exacerbation [median = 125 pg/mL; mean (SD) = 128.6 (43.3) pg/mL] were significantly lower than the follow-up levels during stability [median = 250 pg/mL; mean (SD) = 291.6 (66.7) pg/mL] and both levels correlated positively with each other. The corresponding values of the control group were higher than those of the asthmatic patients whether during exacerbation or stability [median = 380 pg/mL; mean (SD) = 476.1 (259.6) pg/mL]. The serum IL-18 concentrations did not vary significantly according to asthma severity, family history of atopy, or passive smoking. The influence of inhaled corticosteroids on IL-18 expression was not impressive and neither was the relation between serum IL-18 and the peripheral blood eosinophil count or serum total IgE expression. CONCLUSIONS: Serum IL-18 was found underexpressed in a group of asthmatic children especially during exacerbation. Further studies are needed to outline its exact role in the pathogenesis of asthma.